Big Data, Machine Learning, and Artificial Intelligence to Advance Cancer Care: Opportunities and Challenges - Charalambous, Andreas; Dodlek, Nikolina (My University, 2023)
The rapid advances in artificial intelligence (AI), big data, and machine learning (ML) technologies hold promise for personalized, equitable cancer care and improved health outcomes within the context of cancer and beyond. Furthermore, integrating these technologies into cancer research has been effective in addressing many of the challenges for cancer control and cure. This can be achieved through the insights generated from massive amounts of data, in ways that can help inform decisions, interventions, and precision cancer care. AI, big data, and ML technologies offer, either in isolation or in combination, unconventional pathways that facilitate the better understanding and management of cancer and its impact on the person. The value of AI, big data, and ML technologies has been acknowledged and integrated within the Cancer Moonshot program in the U.S. and the EU Beating Cancer Plan in Europe.
Keywords: Artificial intelligence; Big data; Cancer care; Diagnostics; Machine learning; Telemonitoring